2019
DOI: 10.1039/c9ra04435c
|View full text |Cite
|
Sign up to set email alerts
|

Design of ultrathin hybrid membranes with improved retention efficiency of molecular dyes

Abstract: Nanocellulose–graphene oxide ultrathin coatings for water purification membranes with excellent swelling resistance, permeability and dyes retention are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…At present, most of the nanocellulose-based coatings, films, or membrane modification strategies are based on laboratory scale or batch production of the materials, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although printing and papermaking companies have prioritised nanocellulose-based coatings over their synthetic counterparts [32,33]. Transferring the lab-scale approaches to continuous production lines is usually considered a major challenge, [34] which is reflected by only a limited amount of approaches attempted to be translated into industrially viable unit operations [35].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the nanocellulose-based coatings, films, or membrane modification strategies are based on laboratory scale or batch production of the materials, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although printing and papermaking companies have prioritised nanocellulose-based coatings over their synthetic counterparts [32,33]. Transferring the lab-scale approaches to continuous production lines is usually considered a major challenge, [34] which is reflected by only a limited amount of approaches attempted to be translated into industrially viable unit operations [35].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Nanocellulose membranes facilitate rejection through mechanisms involving (i) adsorption on the nanoscaled, charged surfaces (ii) size-exclusion ltration by virtue of the nanoscaled porous networks and (iii) a combination of both methods 11,12 relying on the principles similar to that of charged membranes. Porous substrates such as paper, 13 electrospun mats, 14 and commercially available microltration membranes 15 are successfully used as substrates for nanocellulose-based membrane. Ma et al demonstrated the potential of polysaccharide nanobers, including T-CNF for high ux, low-pressure water purication as a barrier layer on polyacrylonitrile (PAN) and polyethylene terephthalate (PET) nonwoven membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane showed removal efficiency of 98.8, 97.6, and 92.3% for Victoria blue B (VBB), Methyl Violet 2 B (MV2), and Rhodamine 6 G (Rh6 G), respectively (Liu et al, 2019c). TOCNF/GO was also used for the coating of a polyvinylidene difluoride (PVDF) substrate in using the blade coating technique (Liu et al, 2019b). The pristine free-standing TOCNF film exhibits poor permeability.…”
Section: Dye Removal Using Nanocellulose Materialsmentioning
confidence: 99%
“…The membranes showed higher permeability compared to most of the common polymer-based membranes. They offered high retention efficiency of 82-99% for dyes (VBB, Rhodamine B (RhB), Methyl Orange (MO), Rh6G, Methyl Blue (MeB), and Methylene Blue (MB)) (Liu et al, 2019b).…”
Section: Dye Removal Using Nanocellulose Materialsmentioning
confidence: 99%